A comparative ex vivo evaluation of colonization resistance against multidrug-resistant Enterobacterales in fecal samples from various animal species and strategies to augment it - Osbelt, Lisa; Eger, Elias; Homeier-Bachmann, Timo; Schwabe, Michael; Wende, Marie; Hammerschmidt, Baerbel; Vernunft, Andreas; Sivapornnukul, Pavaret; Neumann-Schaal, Meina; Guenther, Sebastian; Strowig, Till; Schaufler, Katharina (Frontiers in Microbiology, 2026)
IntroductionMultidrug-resistant (MDR) pathogens, particularly Escherichia coli and Klebsiella pneumoniae, are increasingly prevalent across human, veterinary, wildlife, and environmental compartments. Although microbiota-based interventions may help limit the spread of MDR bacteria, their application beyond preclinical mouse models remains limited. Colonization resistance (CR) in complex host-associated microbiota, especially in livestock and wildlife, remains poorly understood.MethodsWe investigated in situ CR against MDR Enterobacterales in fecal samples from livestock, wildlife, and humans. Using culture-dependent assays, we assessed the inhibitory capacity of native microbiota, a probiotic candidate, and selected prebiotics against MDR E. coli and K. pneumoniae. Microbial community composition and metabolic profiles were characterized using culture-independent methods, including diversity analyses and quantification of short-chain fatty acids.ResultsCR varied markedly among host groups, with distinct patterns observed across wildlife, livestock, and human samples. The probiotic candidate consistently inhibited MDR E. coli and K. pneumoniae from diverse host sources, whereas prebiotics showed limited effects. Enhanced natural CR and probiotic efficacy were associated with higher microbial diversity, lower baseline abundance of endogenous Enterobacterales, and increased total concentrations of short-chain fatty acids.DiscussionThese findings demonstrate that host-associated microbiota differ substantially in their ability to resist MDR Enterobacterales and that probiotic-mediated inhibition is influenced by microbial and metabolic context. Within a One Health framework, our results highlight the potential of prophylactic probiotic strategies to reduce the spread of MDR pathogens, particularly in livestock settings.